Analysis of Inkjet Printed Polymer Electrolyte Electrolyzer Electrodes. (24th August 2017) - Mandal, Manas; Valls, Antoni; Gangnus, Niklas; Secanell, Marc
Abstract : Inkjet printing (IJP) is studied as a novel fabrication method for catalyst coated membranes (CCMs) for polymer electrolyte electrolyzers. Compared to traditional fabrication methods, such as ultrasonic spray and doctor blade, inkjet's drop-by-drop deposition allows for accurate deposition control, enabling the fabrication of low loading, conventional loading, patterned electrodes, while reducing catalyst waste. CCMs were prepared by IJP by depositing IrO2 and Pt/C inks over the membrane to fabricate anode and cathode electrodes respectively. The anode catalyst layer morphology was analyzed using an optical microscope and scanning electron microscopy (SEM) for surface and thickness characterization. SEM images show the catalyst layer is uniform and well adhered to the membrane. Hydrogen crossover and cyclic voltammetry (CV) tests were performed to estimate hydrogen cross-over, and double layer capacitance. Electrochemical performance tests showed that inkjet printed catalyst coated electrolyzer membranes fabricated achieved 1 and 2 A/cm 2 current densities at potentials of 1608 and 1694 mV (NRE211) and average of 1743 and 1994 mV (N117) respectively. These results outperform most previously reported electrolyzer data in the literature using commercial IrO2 catalyst and suggest that IJP can be used to fabricate electrolyzer electrodes with excellent performance and minimal catalyst wastage.